2021
DOI: 10.2486/indhealth.2021-0072
|View full text |Cite
|
Sign up to set email alerts
|

Surgical masks do not increase the risk of heat stroke during mild exercise in hot and humid environment

Abstract: Surgical masks are widely used for the prevention of respiratory infections. However, the risk of heat stroke during intense work or exercise in hot and humid environment is a concern. This study aimed to examine whether wearing a surgical mask increases the risk of heat stroke during mild exercise in such environment. Twelve participants conducted treadmill exercise for 30 min at 6 km/h, with 5% slope, 35°C ambient temperature, and 65% relative humidity, while wearing or not a surgical mask (mask and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A study with 12 participants who walked on a treadmill for 30 min with and without surgical masks at a speed of 6 km/h in an environment with a room temperature of 35°C and relative humidity of 65%. 6 showed that core body temperature increases regardless of mask wearing, but that the two groups have no significant difference. Another study used an internal capsule‐type core thermometer to measure the body temperature of six participants who completed tasks of standing, walking, and running for 20 min each when not wearing a mask (control), wearing a surgical mask, and wearing a sports mask in an environment with a room temperature of 28°C.…”
Section: Literature Collection and Review Processmentioning
confidence: 94%
See 2 more Smart Citations
“…A study with 12 participants who walked on a treadmill for 30 min with and without surgical masks at a speed of 6 km/h in an environment with a room temperature of 35°C and relative humidity of 65%. 6 showed that core body temperature increases regardless of mask wearing, but that the two groups have no significant difference. Another study used an internal capsule‐type core thermometer to measure the body temperature of six participants who completed tasks of standing, walking, and running for 20 min each when not wearing a mask (control), wearing a surgical mask, and wearing a sports mask in an environment with a room temperature of 28°C.…”
Section: Literature Collection and Review Processmentioning
confidence: 94%
“…Regardless of mask wearing, exercising in a hot environment has a large impact on core body temperature. 4 , 5 , 6 , 7 With the interpretation of the above results that the risk for heat stroke is not sufficiently reduced in a hot environment even if a mask is not worn, it is especially important that older adults, children, and those with lung disease take measures against heat stroke in a hot environment, such as ensuring air conditioning and hydration.…”
Section: Literature Collection and Review Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Rectal temperature (T rec ) was measured continuously using a thermistor probe (701J, Nikkiso-Therm, Tokyo, Japan) self-inserted by the participant to 13 cm beyond the rectal sphincter. Skin temperature (T skin ) at the chest, abdomen, back, forearm, upper arm, thigh, and lower leg were measured every 10 s using a temperature/humidity logger (DS1923 iButton Hydrochron, Maxim Integrated, San Jose, CA, USA) (MacRae et al, 2018;Kato et al, 2021). The temperature/humidity loggers were placed on the skin.…”
Section: Measurementsmentioning
confidence: 99%
“…Also, while Morris et al 16 found no difference in whole body thermal discomfort, they found an increase in perceived breathlessness by 36%. In addition to the Morris et al 16 study, a study performed by Kato et al, 17 found surgical mask use during 30 minutes of mild uphill treadmill exercise did not increase risk of heat stroke in a hot and humid environment. To date, no research study has investigated the effects of surgical mask use during HIIE in different environmental conditions.…”
mentioning
confidence: 92%